2018
DOI: 10.4103/meajo.meajo_267_16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude toward eye donation among adults, Northwest Ethiopia: A community-based, cross-sectional study

Abstract: BACKGROUND:In developing countries, the leading cause of childhood blindness is corneal scarring. Although the service of corneal transplantation depends on several factors, availability of potential donors is of paramount importance. Attitude of eligible donors is the main factor that affects corneal supply. However, limited data exist on eye donation. Hence, this study intended to assess the knowledge and attitude toward eye donation and its associated factors.SUBJECTS AND METHODS:A community-based, cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Similarly study result supported that A communitybased, cross-sectional study was conducted on 760 adults in Gondar town, Northwest Ethiopia shows that 59.9% had good attitude and 40.1% had poor attitude regarding eye donation. 17 Similarly descriptive cross-sectional study was carried out among 400 students of nursing college of Belagavi city India showed that 14.25% had poor Attitude, 71.75% had average and 14% had good Attitude about eye donation 32 .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly study result supported that A communitybased, cross-sectional study was conducted on 760 adults in Gondar town, Northwest Ethiopia shows that 59.9% had good attitude and 40.1% had poor attitude regarding eye donation. 17 Similarly descriptive cross-sectional study was carried out among 400 students of nursing college of Belagavi city India showed that 14.25% had poor Attitude, 71.75% had average and 14% had good Attitude about eye donation 32 .…”
Section: Discussionmentioning
confidence: 98%
“…[ 5 16 19 24 ] Studies from outside India also reported the identical cause. [ 15 17 21 25 ] Saudi Arabia had the highest percentage of 82% that reported deformity as the cause for not pledging eye donation, although the study group comprised of medical and non-medical professionals. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, in the majority of Indian and international studies, the main source of information was the mass media (TV, radio, newspaper, social media). [ 9 11 14 16 17 18 22 23 24 27 28 30 31 32 ] Only Priyadarshini et al . [ 13 ] cited publicity campaign (40.86%) as the primary source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, knowledge of eye donation has been reported to vary from 2.9% 14 to 60%. 15 Eye donation knowledge, such as the process of donation as to who to contact, legal issues including the need for additional consent from the next of kin, 16 optimal timing for donation, criteria for a donation, and contact with an eye bank, is crucial to increasing eye donation rates. 2,9,17 Inadequate knowledge of these aspects of eye donation could contribute to the failure to donate eyes within the narrow donation time frame which can range from 6 hours 14,16 to 24 hours.…”
mentioning
confidence: 99%